Two Sides of the Same Coin: A Case Report of First-Episode Catatonic Syndrome in a High-Functioning Autism Patient - Hefter, Dimitri (Front Psychiatry, 2019)
Background: Catatonic phenomena such as stupor, mutism, stereotypy, echolalia, echopraxia, affective flattening, psychomotor deficits, and social withdrawal are characteristic symptoms of both schizophrenia and autism spectrum disorders (ASD), suggesting overlapping pathophysiological similarities such as altered glutamatergic and dopaminergic synaptic transmission and common genetic mutations. In daily clinical practice, ASD can be masked by manifest catatonic or psychotic symptoms and represent a diagnostic challenge, especially in patients with unknown or empty medical history. Unclear diagnosis is one of the main factors for delayed treatment. However, we are still missing diagnostic recommendations when dealing with ASD patients suffering from catatonic syndrome. Case presentation: A 31-year-old male patient without history of psychiatric disease presented with a severe catatonic syndrome and was admitted to our closed psychiatric ward. After the treatment with high-dose lorazepam and intramuscular olanzapine, catatonic symptoms largely remitted, but autistic traits persisted. Following a detailed anamnesis and a thorough neuropsychological testing, we diagnosed the patient with high-functioning autism and catatonic schizophrenia. The patient was discharged in a remitted state with long-acting injectable olanzapine. Conclusion: This case represents an example of diagnostic and therapeutic challenges of catatonic schizophrenia in high-functioning autism due to clinical and neurobiological overlaps of these conditions. We discuss clinical features together with pathophysiological concepts of both conditions. Furthermore, we tackle social and legal hurdles in Germany that naturally arise in these patients. Finally, we present diagnostic “red flags” that can be used to rationally select and conduct current recommended diagnostic assessments if there is a suspicion of ASD in patients with catatonic syndrome in order to provide them with the most appropriate treatment.